Decision Support System for Determining Disease and Pest Handling in Chili Plants Using WP and VIKOR Methods - Jalila, Muhammad Mulkan; Fuadi, Wahyu; Razi, Ar (ISB Atma Luhur, 2025)
Abstract— Chili plants are an important horticultural commodity that plays a major role in the agricultural and economic sectors of Indonesia. However, the high risk of pest and disease attacks is a major challenge for farmers in increasing productivity. Many farmers have difficulty in determining the right handling strategy, so technology-based solutions are needed to assist the decision-making process. This study developed a Decision Support System (DSS) for handling diseases and pests in chili plants using two methods, namely Weighted Product (WP) and VIšekriterijumsko Kompromisno Rangiranje (VIKOR). The WP method is used to calculate attribute assessments by multiplication, where each criterion is weighted according to its level of importance. The final results show that the best alternative is fusarium wilt disease (Fusarium oxysporum) with code A2, having a vector score of 0.09899. In the VIKOR method, the alternative with the lowest Qi index value is considered the best solution. Alternative A2 is again ranked at the top with a Qi value of 0. The process of developing this DSS involves identifying disease and pest symptom criteria, normalizing the decision matrix, and calculating the ideal solution for each alternative. This approach has proven effective in providing accurate recommendations and helping farmers choose the most optimal management strategy. By utilizing WP and VIKOR-based SPK, it is hoped that chili farmers can increase efficiency in identifying and overcoming plant disorders, so that agricultural productivity can increase significantly.